Discovery and validation of peritoneal endometriosis biomarkers in peritoneal fluid and serum. Issue 4 (October 2021) - Loy, See Ling; Zhou, Jieliang; Cui, Liang; Tan, Tse Yeun; Ee, Tat Xin; Chern, Bernard Su Min; Chan, Jerry Kok Yen; Lee, Yie Hou
Highlights: Untargeted metabolomics uncovers biologically plausible PE biomarker from PF. PF phenylalanyl-isoleucine distinguishes women with PE from controls. Validation of PF phenylalanyl-isoleucine in independent samples. Serum phenylalanyl-isoleucine may be used as a minimally-invasive biomarker of PE. Abstract: Research question: What are the potential biomarkers for peritoneal endometriosis in peritoneal fluid and serum? Design: Case-control studies composed of independent discovery and validation sets were conducted. In the discovery set, untargeted liquid chromatography-mass spectrometry (LC-MS/MS) metabolomics, multivariable and univariable analyses were conducted to generate global metabolomic profiles of peritoneal fluid for endometriosis and to identify potential metabolites that could distinguish peritoneal endometriosis ( n  = 10) from controls ( n  = 31). The identified metabolites from the discovery set were validated in independent peritoneal fluid ( n =19 peritoneal endometriosis and n  = 20 controls) and serum samples ( n  = 16 peritoneal endometriosis and n  = 19 controls) using targeted metabolomics. The area under the receiver-operating characteristics curve (AUC) analysis was used to evaluate the diagnostic performance of peritoneal endometriosis metabolites. Results: In the discovery set, peritoneal fluid phosphatidylcholine (34:3) and phenylalanyl-isoleucine were significantly increased in peritoneal endometriosis groups compared with control groups, with AUC 0.77 (95% CI 0.61 to 0.92; P  = 0.018) and AUC 0.98 (95% CI 0.95 to 1.02; P < 0.001), respectively. In the validation set, phenylalanyl-isoleucine retained discriminatory performance to distinguish peritoneal endometriosis from controls in both peritoneal fluid (AUC 0.77, 95% CI 0.61 to 0.92; P  = 0.006) and serum samples (AUC 0.81, 95% CI 0.64 to 0.99; P  = 0.004), with notably stronger discrimination between peritoneal endometriosis and controls in proliferative phase. Conclusion: Our preliminary results propose phenylalanyl-isoleucine as a potential biomarker of peritoneal endometriosis, which may be used as a minimally invasive diagnostic biomarker of peritoneal endometriosis.